Exposure to grass pollen – but not birch pollen – affects lung function in Swedish children. Issue 9 (11th June 2015) - Gruzieva, O.; Pershagen, G.; Wickman, M.; Melén, E.; Hallberg, J.; Bellander, T.; Lõhmus, M.
Abstract Allergic response to pollen is increasing worldwide, leading to high medical and social costs. However, the effect of pollen exposure on lung function has rarely been investigated. Over 1800 children in the Swedish birth cohort BAMSE were lung‐function‐ and IgE‐tested at the age of 8 and 16 years old. Daily concentrations for 9 pollen types together with measurements for ozone, NO2, PM10, PM2.5 were estimated for the index day as well as up to 6 days before the testing. Exposure to grass pollen during the preceding day was associated with a reduced forced expiratory volume in 8‐yr‐olds; −32.4 ml; 95% CI: −50.6 to −14.2, for an increase in three pollen counts/m³. Associations appeared stronger in children sensitized to pollen allergens. As the grass species flower late in the pollen season, the allergy care routines might be weakened during this period. Therefore, allergy information may need to be updated to increase awareness among grass pollen‐sensitized individuals.